Nursing students' experience of incivility behaviours and its correlation with their nursing professional values: A cross‐sectional descriptive study - Vahid Naseri; Mahsa Boozari Pour; Foroozan Atashzadeh‐Shoorideh; Payam Emami (Wiley, 2023)
Abstract Aims The purpose of this study was to determine the relationship between experienced incivility behaviours and professional values in the clinical setting and also the factors influencing incivility and professional values. Design Cross‐sectional descriptive study. Methods Data gathering tools used in the study includes demographic characteristics, incivility behaviour and nursing professional values. Data were analysed using IBM SPSS version 21. Results The findings showed that incivility behaviours had a statistically significant negative correlation with professional values (r = −.150, p = .003), so that the level of incivility behaviours experienced by students was low (1.76 out of 5). This was while the level of professional values was moderate to high among students (3.72 out of 5). Due to the negative and statistically significant correlation between incivility behaviours experienced by students and nursing professional values, it is necessary that the officials of teaching hospitals inform nurses about incivility behaviours. Considering the negative and statistically significant correlation, it can be concluded that the reduction in nurses' incivility behaviours as patterns of the nursing profession causes nursing students to better acquire and internalize nursing professional values in the clinical setting. Nurse educators should also try to communicate with nursing administrators to exchange information about nurses' civil and incivility behaviours perceived by students.